Friction and Wear Properties of AgCuNi Alloy/Au-Electroplated Layer Sliding Electrical Contact Material - Hongjian Wu; Yanan Zhang; Hui Cao; Han Li; Qingjian Jia; Ming Ma (Lubricants)
Understanding the tribological properties of alloy-based sliding electrical contacts is crucial for both fundamental research and practical applications. Here, to explore the friction, wear, and contact resistance of a AgCuNi alloy/Au-electroplated layer during sliding, a ball-on-disk tribometer was coupled with a source meter. The experiments were conducted under various conditions including a current ranging from 0 to 1.0 A, a normal load ranging from 0.5 to 3.0 N, and a sliding speed of 40 mm/s. The results indicate that the wear of the friction pair is aggravated by both the current and the increase in the normal load. When the current was 0.5 A, the wear loss reached its lowest point. However, as the current increased from 0.5 A to 1.0 A, there was an intensification in Ag transfer from the alloy ball to the Au-electroplated layer, resulting in an increase in wear loss. Both the normal load and current have significant effects on both friction coefficient and contact resistance. The variation in contact resistance over time follows a similar pattern to that of the friction coefficient over time. The formation of a transfer film plays a crucial role in determining contact resistance, wear resistance, and friction coefficient. The experiment demonstrates that optimizing the normal load and current can adjust both the contact resistance and friction coefficient, thereby prolonging service life and ensuring the stability of contacts.